Pengaruh Gaya Kepemimpinan dan Insentif Kerja Terhadap Kinerja Karyawan di SMK Boash One Kabupaten Bogor Tahun 2023-2024 - Meysa Wijaya Kusuma; Immas Nurhayati; Mohammad Jibriel Avessina (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study was conducted to determine the effect of leadership style and work incentives on employee performance at SMK Boash One Bogor Regency. The population used in this study was 155 people, using the simple random sampling method and the slovin formula with an error rate of 10% obtained a sample of 61 people. This research is quantitative using multiple linear regression analysis methods processed using the SPSS 26 statistical application and the data used are primary and secondary data. Data collection techniques were carried out through interviews, questionnaires, and library documentation. The results of this study indicate that leadership style partially has a positive and significant effect on employee performance. The work incentive variable has a positive and significant effect on employee performance partially. Leadership style variables and work incentives simultaneously have a positive and significant effect on employee performance. It can be concluded that leadership style and work incentives have a positive and significant effect on employee performance at SMK Boash One Bogor Regency partially and simultaneously.